Modifications in the metabolism of carbohydrates in (Coffea arabica L. cv. SIRIEMA) seedlings under drought conditions - Fernandes, Christiane Noronha; Melo, Emanuelle Ferreira; Barbosa Barquero, Luis Orlando; Alves, José Donizeti; Júnior, Antonio Chalfun (Coffee Science - ISSN 1984-3909, 2013)
Understanding what mechanisms are involved in drought response in coffee plants will generate relevant information to assist breeding and/or genetic engineering to obtain new commercial varieties with drought tolerance. This research aimed at studying the effects of drought on leaf water potential, carbohydrate concentrations, and sucrose synthase and invertase activity in coffee seedlings (Coffea arabica Siriema), originating from a natural cross between C. racemosa and C. arabica Blue Mountain (Carvalho et al., 2008). Seedlings were grown in a greenhouse under non-irrigated and daily irrigated conditions. Plants were evaluated every three days until they reached the permanent wilting point or, at most. 30 days after withholding water. In addition, plants under different drought conditions (as of 30 days) were irrigated and evaluated 24 and 48 hours after water application. The non-irrigated treatment prompted a significant reduction in leaf water potential, whereas re-irrigation promoted partial recovery of plant water potential. There was a significant increase in the levels of total soluble sugars and reducing sugars, both in the leaves and roots of the non-irrigated plants. The re-irrigated plants behaved like the non-irrigated plants; however, lower levels of sugars were detected in these samples. The leaves and roots of the nonirrigated plants also showed a significant reduction in starch levels. The activity of sucrose synthase and invertase, neutral and acid enzymes, increased as a result of water stress.